iPhone for seniors - Spivey, Dwight (--For dummies., 2025)
iPhone For Seniors For Dummies, 2025 Edition helps you make the most out of your iPhone. You'll learn all about iPhone models and get help in deciding which one suits you best. If you've already got your phone in hand, you're ready to make calls, send text messages, check your e-mail, use FaceTime, track your health and medications, and beyond. The step-by-step instructions are right here. With the help of this clear and accessible Dummies guide, you'll set up your phone and discover all its features. Start making photo and video memories, know what's happening with the weather, and download games and other apps.